WEBVTT
00:00:01.940 --> 00:00:13.040
Simplify eight 𝑦 squared minus three 𝑦 plus two minus three 𝑦 squared plus five 𝑦 plus one.
00:00:14.870 --> 00:00:20.440
In order to simplify this expression, we need to group or simplify the like terms.
00:00:21.650 --> 00:00:26.800
Firstly, we need to subtract three 𝑦 squared from eight 𝑦 squared.
00:00:28.340 --> 00:00:34.250
This is equal to five 𝑦 squared as eight minus three is equal to five.
00:00:35.710 --> 00:00:41.250
Secondly, we need to subtract positive five 𝑦 from negative three 𝑦.
00:00:42.610 --> 00:00:51.680
Negative three 𝑦 minus five 𝑦 is equal to negative eight 𝑦 as negative three minus five is equal to negative eight.
00:00:53.210 --> 00:00:56.670
Finally, we need to subtract one from two.
00:00:57.850 --> 00:00:59.850
This is equal to positive one.
00:01:01.300 --> 00:01:17.200
This means that the simplified version of eight 𝑦 squared minus three 𝑦 plus two minus three 𝑦 squared plus five 𝑦 plus one is equal to five 𝑦 squared minus eight 𝑦 plus one.